2015
DOI: 10.1016/j.apacoust.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

On the use of power reflection ratio and phase change to determine the geometry of a blockage in a pipe

Abstract: Article:Duan, W., Kirby, R., Prisutova, J. et al.(1 more author) (2015) On the use of power reflection ratio and phase change to determine the geometry of a blockage in a pipe. Applied Acoustics, https://doi.org/10.1016/j.apacoust.2014.07.002 eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 18 publications
(39 reference statements)
0
27
0
1
Order By: Relevance
“…9indicates that if the blockage length is a multiple of the half wavelength, then the injected wave is totally transmitted through the blockage. For example, Duan et al (2015) used a blockage detection technique that relies on measuring the reflection coefficient. In the experimental work, Duan et al (2015) varied the central frequency of the generated wave to determine which wave frequencies reflect maximally, which results in maximum reflection (and accuracy) according to the Bragg resonance condition.…”
Section: Analytical Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…9indicates that if the blockage length is a multiple of the half wavelength, then the injected wave is totally transmitted through the blockage. For example, Duan et al (2015) used a blockage detection technique that relies on measuring the reflection coefficient. In the experimental work, Duan et al (2015) varied the central frequency of the generated wave to determine which wave frequencies reflect maximally, which results in maximum reflection (and accuracy) according to the Bragg resonance condition.…”
Section: Analytical Approachmentioning
confidence: 99%
“…For example, Duan et al (2015) used a blockage detection technique that relies on measuring the reflection coefficient. In the experimental work, Duan et al (2015) varied the central frequency of the generated wave to determine which wave frequencies reflect maximally, which results in maximum reflection (and accuracy) according to the Bragg resonance condition. In the experiments, Duan et al (2015) found that for blockage lengths equal to odd integer multiples of the quarter wavelength, the power reflection ratio becomes maximum.…”
Section: Analytical Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique is used to image the human vocal tract system. More recently, the technique elicited considerable interest on the part of water supply researchers (Duan et al 2011(Duan et al , 2013Lee et al 2013;) and its utility was extended to other fields of application (Duan et al 2015).…”
Section: Introductionmentioning
confidence: 99%